ESTIMATION OF ANNUAL EFFECTIVE DOSE DUE TO RADON CONCENTRATION IN GROUNDWATER IN BAUCHI NORTH, NIGERIA. - BABALLE, AUWALU; S. A. DALHATU; IDI, BELLO. Y. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2020)
Radon monitoring has been on increase worldwide because it poses significant health hazard to human being. In this study, radon concentration in wáter was measured to assess the corresponding radiological health implication in the study area. Sixty (60) samples of wáter were analyzed using RAD7, electronic radon detector with special accessory. The measured radon concentration in water samples rangess from 1.8 ± 0.2Bq????−1 to 17.2 ± 1.3Bq????−1 with mean value of 7.2 ± 1.8 Bq????−1. The annual effective dose exposure to individual due to the measured radon concentration was found to be 0.020 mSv ????−1, which is lower than the recommended safe limit of 0.1 mSv????−1 set by WHO and EU council. The level of radon activity concentration in the study area is still within the normal range, thus should not pose any significant health risk to the population.